Examining the Effect of Compensation and Work Motivation on Job Satisfaction and Its Impact on Job Performance: An Evidence from Indonesia - Garaika,; Margahana, Helisia; Haryono, Siswoyo (International Journal of Psychosocial Rehabilitation, 2020)
This study discusses the effect of compensation and work motivation on the performance of lecturers and staff mediated by job satisfaction at the Trisna Negara College of Economics. This study uses two analyzes, namely: descriptive and inferential analysis. This study uses Structural Equation Modeling (SEM) with Smart-PLS 3.2. The population is the lecturers and staff of the Trisna Negara College of Economics. The sampling technique is a purposive sampling method, with a total sample of 100 teachers and staff—data collection techniques using questionnaire distribution. Hypothesis testing employs a significance test with a p-value of 5%. The results of the study are (1) The compensation significantly affects the job satisfaction of lecturers and staff. (2) Work motivation significantly affects the job satisfaction of lecturers and staff. (3) The composition significantly affects the performance of lecturers and staff. (4) Work motivation significantly affects the performance of lecturers and staff. (5) Job satisfaction significantly affects the job performance of lecturers and staff. (6) Job satisfaction mediated the effect of compensation on the performance of lecturers and staff, but job satisfaction did not mediate the effect of motivation on the performance of lecturers and staff. The most dominant total effect was on the path of the effect of compensation on job performance through job satisfaction.